ACTIVITY BASED COSTING METHOD IN DETERMINING ROOM SERVICE COSTS. (Study Kasus at Hotel Wilis Indah Abadi In Nganjuk) - Novia Maysaroh; Tjandra Wasesa; Diana Zuhro; Sutini Sutini; Annisa Rachmawati; Achmad Daeng GS (Journal of Managerial Sciences and Studies, 2026)
The object of this research is the Wilis Indah Abadi Hotel located in Nganjuk. So far, in determining the cost of room service, the traditional system is still used based on the costs incurred and identifying costs so that the determination of the cost of room service does not reflect the actual costs used by each room activity. The purpose of this study is to calculate and analyze the determination of the cost of room service using the activity based costing method and to find out the differences between the traditional and activity based costing methods. Researchers will identify costs, allocate costs based on their respective cost drivers and calculate using the activity based costing method according to the theory. So that the differences in determining the traditional method with the activity based costing method can be known. The results of this study indicate that there are differences between the traditional method and the activity based costing method, including: Teratai 5,241.13, Alamanda (5,228.11). Tulip (6,190.93) Pavilion 7,589.58.